2015
DOI: 10.1016/j.jpeds.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic and Fitness Improvements in Obese Girls Who Either Gained or Lost Weight during Treatment

Abstract: Objective To evaluate the quality of weight change (change in fat mass vs. fat-free mass [FFM]), changes in cardiorespiratory fitness (CRF), and frequencies of metabolic risk factors in adolescent females with obesity that either lost weight or gained weight following lifestyle treatment. Study design Fifty-eight girls (mean age = 13.0 ± 1.6 yrs; 77% black; mean body mass index (BMI) = 36.5 ± 4.5 kg/m2) completed a 6-month lifestyle intervention combining dietary and behavioral counseling with aerobic and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
1
3
0
3
Order By: Relevance
“…In the present investigation, the lack of improvement in indices of cardiometabolic health may be related to the lack of overall weight loss, despite improvements in adiposity in both groups. This notion is corroborated by previous research in youth with OB (52,53) and could be further explored in the context of weight loss and dairy consumption.…”
Section: Discussionsupporting
confidence: 82%
“…In the present investigation, the lack of improvement in indices of cardiometabolic health may be related to the lack of overall weight loss, despite improvements in adiposity in both groups. This notion is corroborated by previous research in youth with OB (52,53) and could be further explored in the context of weight loss and dairy consumption.…”
Section: Discussionsupporting
confidence: 82%
“…Alberga et al (2012) 26 Alberga et al (2015) 27 Antunes et al (2013) 28 Antunes et al (2015) 29 Bell et al (2007) 30 Browning et al (2015) 31 Bruyndonckx et al (2015) 32 Campos et al (2014) 33 Dâmaso et al (2014) 12 Davis et al (2011) 34 Foschini et al (2010) 35 Gow et al (2016) 36 Inoue et al (2015) 37 Mello et al (2011) 38 Mendelson et al (2015) 39 Monteiro et al (2015) 40 Piano et al (2012) 41 Sigal et al (2014) 42 Son et al (2017) 43 Calcaterra et al (2013) 44 Prescription of sports activities only Reinehr et al (2011) 45 Carrel et al (2005) 46 Resistance training and sports activities 48 Gueugnon et al (2012) 49 Huang et al (2015) 50 Kamal & Ragy. (2012) 51 Kelishadi et al (2008) 52 Knox et al (2012) 53 Mccormack et al (2014) 54 Vrablík et al (2014) 55 -n = 26 non-active male adolescents who did not participate in structured physical activities (16.0 ± 1.0 years) -They were randomized into five groups (HIIT + TR, HIIT + TR, HIIT + TR, HIIT + TR, and HIIT + TR).…”
Section: Sample Characteristics and Exercise Detailsmentioning
confidence: 99%
“…41 A recent study similarly demonstrated improvements in cardiorespiratory fitness (VO 2 peak) and decreases in low-density lipoprotein and fasting glucose among successful participants in a behavioral weight control program. 42 …”
Section: Lifestyle Interventions For Pediatric Weight Controlmentioning
confidence: 99%